The Fatigue Strength of AISI 430—304 Stainless Steels Welded by CO₂ Laser Beam Welding - Caligulu, U.; Turkmen, M.; Ozer, A.; Taskin, M.; Ozer, M. (Металлофизика и новейшие технологии, 2015)
In this study, the fatigue strength of AISI 430—304 stainless steels welded by CO₂ laser beam welding (LBW) is investigated. Laser welding experiments are carried under helium atmosphere at 2000, 2250 and 2500 W welding powers with 100 cm/min welding speed. The welding zones are examined by optical microscopy, scanning electron microscopy, and energy dispersive spectroscopy analysis. Fatigue tests are performed using an axial fatigue test machine, and the fatigue strength is analysed drawing S−N curves and critically observing fatigue fracture surfaces of the tested samples. The experimental results indicate that mechanical properties and microstructural features are affected significantly by welding power. The fatigue strength of CO₂ laser welded samples increase due to higher deep penetration in welding zone with increasing welding power in chosen conditions. The best properties are observed with the specimens welded at 2500 W heat input and 100 cm/min welding speed.